Biomass for renewable energy, fuels, and chemicals - Klass, Donald L. (Academic Press, 1998)
Biomass for Renewable Energy, Fuels, and Chemicals serves as a comprehensive introduction to the subject for the student and educator, and is useful for researchers who are interested in the technical details of biomass energy production. The coverage and discussion are multidisciplinary, reflecting the many scientific and engineering disciplines involved. The book will appeal to a broad range of energy professionals and specialists, farmers and foresters who are searching for methods of selecting, growing, and converting energy crops, entrepreneurs who are commercializing biomass energy projects, and those involved in designing solid and liquid waste disposal-energy recovery systems. Key Features * Presents a graduated treatment from basic principles to the details of specific technologies * Includes a critical analysis of many biomass energy research and commercialization activities * Proposes several new technical approaches to improve efficiencies, net energy production, and economics * Reviews failed projects, as well as successes, and methods for overcoming barriers to commercialization * Written by a leader in the field with 40 years of educational, research, and commercialization experience.
Keywords: Biomass energy.; Biomass chemicals.; elektronické knihy; electronic books